Kepelbagaian ikan di Tasik Chini,Pahang,Malaysia - Ahmad Abas Kutty,; Mohd Shuhaimi Othman,; Mohd Barzani Ghasim,; Sambau Dugat, (Universiti Kebangsaan Malaysia, 2009)
A study on fish diversity and distribution in Lake Chini was undertaken using gill net as capture tools. Eight sampling stations (various habitats) were chosen within the lake system and random sampling was undertaken at selected area. A total 24 fish species were recorded during the sampling, which comprises of 944 individuals. Majority of fish were represented by the Cyprinidae and Thynnichthys thynnoides, Cyclocheilichythys apogon and Notopterus notopterus were the most family dominance species recorded in Lake Chini. Paired t-test analysis demonstrates that there is a significant fish density difference between day time and night time sampling (p = 0.01, α = 0.05) and predators were dominant during night time. Fish diversity and density were high during monsoon season catch, as a result of immigrant fish of Sungai Pahang to Lake Chini through Chini River.